Unveiling the landscape of antistigma interventions for individuals with substance use disorders: A scoping review - Abhishek Ghosh; Babita Sharma; Arshia Sood; Kshitiz Sharma (Indian Journal of Psychiatry)
Background: Stigma against persons living with substance use disorders (PLSUD) fosters social and health inequities. Aim: We aimed to map different populations targeted by antistigma interventions, analyze specific characteristics of these interventions, and identify and categorize the theoretical frameworks used in these interventions. Methods: We examined randomized controlled trials and quasi or pre-experimental studies targeting stigma against PLSUD. Using two English databases, our analysis involved mapping study populations, antistigma interventions, and trial characteristics through a narrative synthesis. We adhered to the Workgroup for Intervention Development and Evaluation Research (WIDER) checklist for assessing reporting quality. The Theoretical Domain Framework (TDF) identified intervention domains and constructs of the interventions. Results: Of 698 studies, 29 met eligibility, with three from low-middle-income countries: 12 studies addressed the public, 11 self, and 5 structural stigmas. Reduction in stigma or improvements in knowledge of and attitude toward PLSUD was observed in 23 studies. Eight used social contact-based interventions, and one used direct social contact. Other interventions were psychoeducation, collaborative community care and linkage to social services, acceptance and commitment therapy, and gatekeepers’ training. Five focused on injection drug use stigma; others were not substance-specific. Most studies reported the characteristics of the recipients (n = 28), mode of delivery (n = 28), and delivery settings (n = 24). Adherence to delivery protocol was the least reported (n = 5). The number of theoretical domains varied: 18 studies had 1–5 domains, 3 studies had 10, and 8 studies had 6–9 domains. Conclusion: Social contact-based interventions show promise for PLSUD; future research must improve the quality of reporting and design theory-informed interventions.